Z kart parafii unickiej pw. Wniebowzięcia Najświętszej Marii Panny w Gródku w świetle osiemnastowiecznych wizytacji kościelnych - Frykowski, Janusz Adam (Saeculum Christianum. Pismo Historyczne, 2016)
Gródek is a country village whose origin dates back to at least the fifteen century. The first written record of the village dates from 1409. In it is found acknowledgment of Wołczko Rekutowicz from Gródek as one of the founders and a supplier of furnishings to the local church. Originally belonging to the Duchy of Belz, the village together with the Duchy, was incorporated into the Crown of the Kingdom of Poland in 1462. After the first partition of Polish- Lithuanian Commonwealth, Gródek was annexed by the Habsburg Empire, then it became part of the Duchy of Warsaw and following the joint resolutions of the Congress of Vienna it was given to Russia. Today the village situated at the Huczwa river administratively belongs to Jarczow gmina (commune) as part of Tomaszów poviat in Lubelskie Province. During the period the piece of research covers, Gródek was mostly inhabited by Russian people and was an Orthodox parish. It in turn became a Greek Catholic parish following the Union of Brest. The first written record of an Orthodox Church comes from 1507 while 17th century documents confirm the existence of a Uniate parish. Having analyzed post- visitation protocols, it might be deduced that it was a wooden church poorly equipped with ecclesiastical utensils. There was also a bell tower and a cemetery alongside the church. It has been determined a paroch (parish priest) had some arable land as well as grassland at his disposal to support himself. Furthermore, he collected various ecclesiastical fees from his parishioners. From the period of time this research is focused on, personal information of 4 parochs as well as the approximate number of parishioners that varied between 14 and 70 has been established. Furthermore, the church is known to have been functioning in 1772 but it fell into ruin before 1798 after which the parishioners from Gródek attended the branch church in Podlodów.